The 11+ of the future: a primary injury prevention framework for sub-elite football - Whalan, M.; Lovell, R.; Thorborg, K.; Sampson, J. A. (British Journal of Sports Medicine, 2021)
Originally developed as a way to integrate injury risk mitigating exercises into the warm-up, the 11+ importantly reduces injury incidence and burden by ~40% in men`s sub-elite football. Despite its efficacy as a primary injury mitigation strategy, challenges remain regarding 11+ compliance and adoption. This editorial presents a new framework that modernises the programme and tackles issues related to 11+ adoption.